Implementation of Subject-Oriented Methods in the Educational Process of University (Quantitative Results of the Investigation): Case Study - Valeeva, Elvira M; Milyaeva, Ekaterina G; Penner, Regina V; Sosnovskih, Elena G (European journal of contemporary education, 2020)
The authors place the problem of a subject-oriented model in educational process of higher education. The transition to subject-oriented methods is due to the transformations of modernity. Objective changes in reality, informatization and technological changes, require from students fundamentally new knowledge and skills, which the classical educational model cannot provide. This research presents the quantitative results of an educational investigation that was conducted with the aim of finding and testing the optimal forms in teaching humanities in university. The investigation was attended with students who studied the course of philosophy in the Academic Year 2018-2019; we used different forms and methods of working with philosophical material: from classical to non-classical (philosophical practice). In the investigation, we used philosophical practice as an alternative method of teaching philosophy. The non-classical nature of philosophical practice is manifested in the fact that attention is switched from the studied material to the subject of study. In those student groups where methods and techniques from philosophical practice were used, we fixed the students' attention not on the abstract philosophical concepts, but on the specifics of the perception of these concepts by the students themselves. In this way, we narrowed the distance between the theoretical level of philosophical knowledge and the real existential experience of modern students. In the process of the investigation, we paid attention to the independent work of students in the educational process. The materials of the investigation can be used as recommendations for the organization of extracurricular work, focused on the formation of soft skills among students (including discussion and philosophical clubs for the development of critical thinking, logic and other open intellectual creative platforms).